The Effect of Active Video Game (Xbox Kinect) on Static and Dynamic Balance in Children with Autism Spectrum Disorders - Neda Ghobadi; Farhad Ghadiri; Rasoul Yaali; Ahmadreza Movahedi (Vesnu Publications, 2020)
Introduction: Autism spectrum disorders are of neuro-developmental conditions with the most prevalence among the children during recent years. Children with autism spectrum disorders usually have mobility problems in balance. The purpose of this study was to investigate the effect of active video game on static and dynamic balance in children with autism spectrum disorders. Materials and Methods: This was a semi-experimental research with pretest-posttest design and control group. 16 children with autism spectrum disorders, aged 6-10 years, were selected and after pretest of static and dynamic balance, randomly assigned to two equal groups of experimental and control. Experimental group received its respective intervention program [athletics, bowling, and boxing as video game (Xbox Kinect)] 2 sessions a week, lasting 45 minutes, over an 8-week period. Control group performed their daily activities. Modified stork test to measure static balance and walking heel to toe test were used to measure dynamic balance. Data were analyzed using one-way analysis of variance test with significance level of less than 0.05. Results: Significant differences were found between control and experimental groups in static (P = 0.001) and dynamic (P = 0.001) balance. Conclusion: Based on the results of this study, it can be stated that active video game may bring benefits on static and dynamic balance in children with autism spectrum disorders. Therefore, in order to develop balance in children with autism spectrum disorders, the use of active video game is suggested.